Approches méthodologiques de la transgression spatiale - Westphal, Bertrand (Primerjalna književnost, 2004)
Methodological approaches to spatial transgression. After a short semantic overview of transgression, which results in an analysis of the notion of threshold, the article closely examinesthe relations between space and transgression. Scrutinizing the idea of transgression in a socio-poetic framework by using the example of the hospitality code, the author focuses on the dynamics of whole large units, as elaborated by Y. Lotman (semiospheres), I. Even-Zohar (polysystem) and by G. Deleuze and F. Guattari (the dialectic of deterritorialization). In conclusion, the analysis is related to the views of transgression as an imagological and geocritical notion
Keywords: književnost; literature; metodologija; prostor; imagologija